MOTHERS’ EXPERIENCES IN HANDLING OF EXPRESSED BREAST MILK FOR PREMATURE INFANT IN NEONATAL INTENSIVE CARE UNIT: CONTAMINATION OF HUMAN BREASTMILK - Siti Azuna Abu Bakar; Muda, Siti Mariam; Mohd Arifin, Siti Roshaidai; Ishak, Shareena; Ismail, Hamizah (International Journal of Allied Health Sciences, 2019)
Expressed breast milk (EBM) is important for premature infants as it reduces morbidities and mortalities. It is the main nutritional source for them to improve their growth and neurodevelopment, decreases the risk of necrotising enterocolitis and late-onset sepsis. There is limited research found which relates to the real issues faced by mothers while handling their EBM at home. This study aims to explore the experiences of mothers in handling their EBM during the treatment period of their premature infants in NICU. This study was carried out as qualitative research. The face to face in-depth semi-structured interviews were conducted with the mothers. The data were analysed with thematic analysis. Participants: Mothers of premature infants admitted and received treatment in NICU. One of the teaching hospitals in Kuala Lumpur. Four major themes emerged from the mother’s interview data in common error while handling their EBM; cleaning and sterility, expressing, packaging, storage and transportation. Expressing breast milk should be recognized as an important way to restructure motherhood with a preterm infant in NICU. However, poor hygiene on handling EBM increases the growth of bacteria and the occurrence of infections hence putting the premature infants at high risks. Exploring the experiences and compelling stories of the mothers’ routines in handling EBM increased the evidence base regarding the concurrent issue. Health promotion in the NICU is necessary to increase a mother’s awareness of properly managing their EBM.